2015
DOI: 10.1016/j.otsr.2014.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Preventing surgical-site infections: Measures other than antibiotics

Abstract: Surgical-site infections (SSIs) due to intra-operative contamination are chiefly ascribable to airborne particles carrying microorganisms, mainly Staphylococcus aureus, which settle on the surgeon's hands and instruments. SSI prevention therefore rests on minimisation of airborne contaminated particle counts, although these have not been demonstrated to correlate significantly with SSI rates. Maintaining clear air in the operating room classically involves the use of ultra clean ventilation systems combining l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 34 publications
1
56
0
4
Order By: Relevance
“…Although a statistically significant reduction in CFU/m 3 was not observed, these results are encouraging and a larger sample size is required to further investigate these preliminary findings and reduce the likelihood of a type II error. Furthermore, studies have found significant correlations between particle counts and airborne bacteria . Hansen et al found that both ultra‐fine particles and particles larger 5 μm were good surrogates for airborne bacteria and viruses as bacteria are 0.2–5 μm in size and often adhere to larger particles larger than 5 μm to form aggregates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although a statistically significant reduction in CFU/m 3 was not observed, these results are encouraging and a larger sample size is required to further investigate these preliminary findings and reduce the likelihood of a type II error. Furthermore, studies have found significant correlations between particle counts and airborne bacteria . Hansen et al found that both ultra‐fine particles and particles larger 5 μm were good surrogates for airborne bacteria and viruses as bacteria are 0.2–5 μm in size and often adhere to larger particles larger than 5 μm to form aggregates.…”
Section: Discussionmentioning
confidence: 99%
“…The particle counter sampled the air for 1 min and rested for 9 min until the subsequent sample collection. It recorded particles in the size range of 0.5–10 μm, which corresponds to the size range of bacteria and bacteria‐laden particles . TPC included both viable (e.g., bacteria or skin cells) and non‐viable (e.g., dust) particles.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although surgical-site bacterial counts correlate with airborne bacteria and particle counts [35], they have not been demonstrated to correlate directly with the rate of SSIs [4]. The actual relationship among the amount of particles, the incidence of bacterial contamination, and the rate of SSIs was not addressed in this study.…”
Section: Discussionmentioning
confidence: 94%
“…However, airborne particles can act as vectors for transmission of bacteria after coming in contact with unsterile areas (e.g. skin, walls, or floor) [4]. Particles settled on an unsterile floor can be easily dispersed by air eddies generated from opening doors and foot traffic.…”
Section: Discussionmentioning
confidence: 99%